Mechanisms Underlying Potential Therapeutic Approaches for COVID-19 - Benani, Abdelouaheb; Ben Mkaddem, Sanae (Frontiers in Immunology, 2020)
Coronavirus disease (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is a betacoronavirus, and is associated with cytokine storm inflammation and lung injury, leading to respiratory distress. The transmission of the virus is mediated by human contact. To control and prevent the spread of this virus, the majority of people worldwide are facing quarantine; patients are being subjected to non-specific treatments under isolation. To prevent and stop the COVID-19 pandemic, several clinical trials are in the pipeline. The current clinical trials either target the intracellular replication and spread of the virus or the cytokine storm inflammation seen in COVID-19 cases during the later stages of the disease. Since both targeting strategies are different, the window of the administration of the drug plays a crucial role in the efficacy of the treatment. Here, we review the mechanism underlying SARS-CoV-2 cell infection and potential future therapeutic approaches.